Diseño de plan de marketing turístico y su Impacto en los micro emprendedores de Montalvo, año 2022. - Suárez Quiroz, José Felix (2022)
Currently the tourism sector is rising after the health emergency known as Covid-19 which had a negative impact due to the fact that the number of visitors was limited, this led to an economic crisis. The Montalvo canton is known for being a tourist destination to enjoy with family, friends and the general public, therefore, tourist activity in this canton is fundamental and the main source of economy since it needs to encourage tourism, therefore, the The objective of this thesis is to design a tourism marketing plan and its impact on the micro-entrepreneurs of Montalvo, to improve and position tourism in the aforementioned canton.